Compreensão do trabalho dos aeroviários no atendimento aos passageiros com necessidade de assistência especial: uma perspectiva da atividade - Figueiredo, Júlia Pierre (Universidade Federal de São Carlos, 2018)
The price reduction of air tickets in Brazil has raised the flow of passengers, as well as the diversity of people utilizing kind of transport. Some specific groups need differentiated services in relation to others and face several difficulties during air travel. Some of these difficulties are related to services provided by air service employees, airline workers responsible for ground services inside the terminal. The aim of the present study was to understand the work activity of air service employees in the aid of these specific groups of passengers, encompassed in the denomination of PNAEs (Passengers with Special Needs). The research has a qualitative approach and the work was studied in light of the Theory of Activity and of concepts of Activity Ergonomics. The method of the study was the Ergonomic Work Analysis (AET), and the data collection took place in 11 Brazilian airports, distributed in the 5 major regions of the country. Observations and interviews were carried out and posteriorly analyzed by the method of content analysis. The results describe the task and the work activity of airline service employees in all steps of the attendance process, including the check-in attendance, the guidance of passengers inside the terminal, the boarding procedure, the flight dispatch, and the disembarkation of passengers. The results also identified contradictions and discontinuities in the systems of activities, which constrain the work of the air service employees, generating difficulties and conflicts. The main factors that cause conflicts are: the lack of resources and conditions necessary for the air service employees to carry out their work, and the lack of information of passengers related to the procedures to be followed in the complex context of aviation. The study brought contributions to the understanding of the work of the air service employees, little discussed in the literature, and the approach in light of the perspective of the activity made it possible to confront the logics of different social actors of air transport, giving a broad view of the work context, and the interactions between its elements.
Keywords: Passageiros com deficiência; Trabalho de aeroviários; Transporte aéreo; Ergonomia; Atividade; Passengers with disabilities; Activity; Air transport; Ergonomics; Work of air service employees; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA